2-Methyl-1, 4, 4a, 9a-tetrahydroanthracene-9, 10-dione (Me-THAD) as a catalyst in alkaline chemical pulping. (5th November 2021) - Francis, Raymond C.; Schnelle, Scott T.; Nicholson, Daniel J.; Agblevor, Foster A.; Kiemle, David J.
Abstract: The objective of this investigation was to assess the feasibility of replacing anthraquinone (AQ) as a yield enhancing catalyst in kraft pulping with Me-THAD. It was anticipated that residual Me-THAD on the washed pulp fibers would be air-oxidized to 2-methyl-anthraquinone (MAQ) during commercial fiber drying. While AQ is listed as a possible human carcinogen by the International Agency for Research on Cancer (IARC), MAQ is not. Also, MAQ was reported to actually retard the propagation of cancer cells in more than one refereed publication. In this study, it was observed that both of the methyl-substituted catalysts (MAQ and Me-THAD) were equal or more effective than AQ at increasing fiber yield when added to kraft pulping of both a softwood (southern pine) and a hardwood (eucalyptus). It was observed that pure Me-THAD powder oxidized to MAQ at room temperature (∼22 °C). The inference was drawn that residual Me-THAD on washed fibers from kraft/Me-THAD pulping also oxidized to MAQ. Extracts from such fibers from a eucalyptus pulp were carefully analyzed on a Thermo Scientific Trace 1310 with Orbitrap GC/MS. The unbleached fibers contained 20 μg/kg (ppb) of MAQ and ∼1 μg/kg of Me-THAD. When bleached using the D0 EpD1 sequence to 90% Elrepho brightness, the fibers contained 3.5 μg/kg of MAQ and no Me-THAD. A preliminary assessment on the economics of Me-THAD synthesis at commercial scale is included.